New Technology: Its Effects on Use and Mangement of the Radio Spectrum - Leland L. Johnson (Washington University Law Quarterly, 1967)
In this Article, Mr. Leland Johnson describes some of the problems in using radio spectrum and ways in which new technologies may be utilized to relieve today's scarcity of usable spectrum. He discusses the enormous potentialities of non-spectrum transmission devices, particularly cable transmission.
Keywords: Frequency allocation (Telecommunications); Radio broadcasting